2006
DOI: 10.3233/jae-2006-737
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and study of a single TiO_{2}-coated optical fiber reactor

Abstract: A TiO _{2} -coated optical fiber photoreactor was built and studied in order to optimize different parameters before the development of a multi-optical fiber reactor. The physico-chemical properties of the TiO _{2} film prepared by a sol-gel method on an optical fiber were first determined. A thickness of about 30 nm per layer and a roughness of 2 nm were estimated by ESEM and AFM, respectively. The refractive index of the TiO _{2} coating was determined by a simulation method. Then, the influences of the film… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…The use of a single or bundle of optical fibres for the remote delivery of light to reactive sites of coated photocatalysts has been studied by several researchers for wastewater treatment and CO 2 photocatalysis [48,154,[215][216][217]. All researchers observed increased degradation and conversion rates when the optical fibres were simultaneously used as a support and light distributing guide.…”
Section: Optical Fibresmentioning
confidence: 96%
“…The use of a single or bundle of optical fibres for the remote delivery of light to reactive sites of coated photocatalysts has been studied by several researchers for wastewater treatment and CO 2 photocatalysis [48,154,[215][216][217]. All researchers observed increased degradation and conversion rates when the optical fibres were simultaneously used as a support and light distributing guide.…”
Section: Optical Fibresmentioning
confidence: 96%
“…A single TiO 2 -coated fiber-optic reactor was designed by Danion et al [21]. The TiO 2 -coated optical fiber photoreactor was built and further studied in order to optimize different parameters before the development of a multi-optical fiber reactor [22][23][24][25]. Peill and Hoffmann demonstrated that TiO 2 -coated optical-fiber reactors had some inherent advantages over packed-bed reactors in photoreactions [26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Diatomite powder is highly porous and can naturally act as a good adsorbent, particularly on slush. It was therefore mixed with slush for thirty minutes [5,6]. Finally, slush was calcined at 450˚C for 30 min.…”
Section: Samples Preparationmentioning
confidence: 99%
“…Furthermore, devoted researchers have spent considerable efforts to accomplish extensive research, and the technology of immobilization of photocatalysic TiO 2 nano-particles seemed the most successful photocatalysis reported on solids since then [3,4]. Various techniques have been developed for the immobilization of TiO 2 on a solid substrate including dip coating suspension [5,6], spray coating and sol-gel. Moreover, different types of substrates were tested such as glass beads [7], glass tubes [8], fiber glass [9], quartz [10], stainless steel [11], aluminum [12], activated carbon [13], silica [14] and glass plates [15] and modified diatomite [16,17].…”
Section: Introductionmentioning
confidence: 99%